Coping with Stress in Deprived Urban Neighborhoods: What Is the Role of Green Space According to Life Stage? - Roe, Jenny J.; Aspinall, Peter A.; Ward Thompson, Catharine (Frontiers in Psychology, 2017)
This study follows previous research showing how green space quantity and contact with nature (via access to gardens/allotments) helps mitigate stress in people living in deprived urban environments (Ward Thompson et al., 2016). However, little is known about how these environments aid stress mitigation nor how stress levels vary in a population experiencing higher than average stress. This study used Latent Class Analysis (LCA) to, first, identify latent health clusters in the same population (n=406) and, second, to relate health cluster membership to variables of interest, including four hypothetical stress coping scenarios. Results showed a three-cluster model best fit the data, with membership to health clusters differentiated by age, perceived stress, general health, and subjective wellbeing. The clusters were labelled by the primary health outcome (i.e. perceived stress) and age group 1) Low-stress Youth characterised by ages 16-24; 2) Low-stress Seniors characterised by ages 65+ and 3) High-stress Mid-Age characterised by ages 25 to 44. Next, LCA identified that health membership was significantly related to four hypothetical stress coping scenarios set in people’s current residential context: ‘staying at home’ and three scenarios set outwith the home, ‘seeking peace and quiet’, ‘going for a walk’ or ‘seeking company’. Stress coping in Low Stress Youth is characterised by ‘seeking company’ and ‘going for a walk’; stress coping in Low-stress Seniors and High Stress Mid-Age is characterised by ‘staying at home’. Finally, LCA identified significant relationships between health cluster membership and a range of demographic, other individual and environmental variables including access to, use of and perceptions of local green space. Our study found that the opportunities in the immediate neighbourhood for stress reduction vary by age. Stress coping in youth is likely supported by being social and keeping physically active outdoors, including local green space visits. By contrast, local green space appears not to support stress regulation in young-middle aged and older adults, who choose to stay at home. We conclude that it is important to understand the complexities of stress management and the opportunities offered by local green space for stress mitigation by age and other demographic variables such as